‘I sold my iris; now what?’: What drives Brazilians to hand over their unique, personal data - Agência Mural (Global Voices, 2025)
Residents of São Paulo's outskirts explained why they chose to give over their personal data to the World ID project. Around 400,000 Brazilians sold their iris data for cryptocurrency.